Investigation of phosphoproteome in RAGE signaling - Batkulwar, Kedar B.; Bansode, Sneha B.; Patil, Gouri V.; Godbole, Rashmi K.; Kazi, Rubina S.; Chinnathambi, Subashchandrabose; Shanmugam, Dhanasekaran; Kulkarni, Mahesh J. (Proteomics, 2015)
The receptor for advanced glycation end products (RAGE) is one of the most important proteins implicated in diabetes, cardiovascular diseases, neurodegenerative diseases, and cancer. It is a pattern recognition receptor by virtue of its ability to interact with multiple ligands, RAGE activates several signal transduction pathways through involvement of various kinases that phosphorylate their respective substrates. Only few substrates have been known to be phosphorylated in response to activation by RAGE (e.g., nuclear factor kappa B); however, it is possible that these kinases can phosphorylate multiple substrates depending upon their expression and localization, leading to altered cellular responses in different cell types and conditions. One such example is, glycogen synthase kinase 3 beta which is known to phosphorylate glycogen synthase, acts downstream to RAGE, and hyperphosphorylates microtubule-associated protein tau causing neuronal damage. Thus, it is important to understand the role of various RAGE-activated kinases and their substrates. Therefore, we have reviewed here the details of RAGE-activated kinases in response to different ligands and their respective phosphoproteome. Furthermore, we discuss the analysis of the data mined for known substrates of these kinases from the PhosphoSitePlus (http://www.phosphosite.org) database, and the role of some of the important substrates involved in cancer, diabetes, cardiovascular diseases, and neurodegenerative diseases. In summary, this review provides information on RAGE-activated kinases and their phosphoproteome, which will be helpful in understanding the possible role of RAGE and its ligands in progression of diseases.
Keywords: Cell biology; Disease; Glycation; Kinase; Phosphoproteome; RAGE

Possible role of glycation in the regulation of amyloid beta precursor protein processing leading to amyloid beta accumulation - Patil, Gouri V.; Joshi, Rakesh S.; Kazi, Rubina S.; Kulsange, Shabda E.; Kulkarni, Mahesh J. (Medical Hypotheses, 2020)
Alzheimer's disease (AD) is one of the most common forms of neurodegenerative diseases amongst the aged population. The disease is multifactorial, and diabetes has been considered as one of the major risk factors for the development of AD. Chronic hyperglycemic condition in diabetes promotes non-enzymatic protein modification by glucose termed as glycation, which affects protein structure and function. Previous studies have shown that many of the enzymes, including proteases, are affected by glycation. Conversely, glycated proteins are known to become resistant to protease action. In these hypotheses, we have extended these two concepts to the regulation of amyloid-beta protein precursor (A beta PP) by secretases leading to amyloid-beta (Af3) accumulation. The first hypothesis deals with the glycation of alpha-secretases leading to its reduced activity, while in the second hypothesis, A beta PP glycation may prevent a-secretases action, rendering its processing by beta secretase. As diabetes is a risk factor for the development of AD, either or both these pathways may operate, leading to the manifestation of AD.
Keywords: Alpha-secretase; Alzheimer `s disease; Amyloid-beta; Amyloid-beta protein precursor; Beta-secretase; Diabetes; glucose; Glycation; Type-3 diabetes